1995
DOI: 10.2166/wst.1995.0412
|View full text |Cite
|
Sign up to set email alerts
|

Formation of 2,4,6-trichlorophenol and 2,4,6-trichloroanisole during treatment and distribution of drinking water

Abstract: Biomethylation of 2,4,6-trichlorophenol to the potent off-flavour compound 2,4,6-trichloroanisole has previously been found to cause taste and odour problems in drinking water. In the present study, both compounds were detected in seemingly unpolluted surface waters. However, the highest concentrations of 2,4,6-trichloroanisole in tap water were caused by the formation of 2,4,6-trichlorophenol during chlorine disinfection of drinking water and subsequent methylation of this compound in the distribution system.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0
1

Year Published

1997
1997
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 0 publications
0
19
0
1
Order By: Relevance
“…It was also noticed that water treatment resulted in a decrease in 2,4,5-TCP content, whereas in drinking water of Warsaw (in January and March) as well as in drinking water of Tomaszów Mazowiecki (in January) the formation of 2,4,6-TCP was observed (Table 4). Similarly, Karlsson et al (1995) observed the formation of 2,4,6-TCP in drinking water during its disinfection with chlorine oxidants. Determined concentrations of 2,4,6-TCP (Table 4) were comparable to its amount detected in 12 Canadian distribution systems ranging from a trace to 3 μg/L (Alberta Environment 1985).…”
Section: Resultsmentioning
confidence: 81%
“…It was also noticed that water treatment resulted in a decrease in 2,4,5-TCP content, whereas in drinking water of Warsaw (in January and March) as well as in drinking water of Tomaszów Mazowiecki (in January) the formation of 2,4,6-TCP was observed (Table 4). Similarly, Karlsson et al (1995) observed the formation of 2,4,6-TCP in drinking water during its disinfection with chlorine oxidants. Determined concentrations of 2,4,6-TCP (Table 4) were comparable to its amount detected in 12 Canadian distribution systems ranging from a trace to 3 μg/L (Alberta Environment 1985).…”
Section: Resultsmentioning
confidence: 81%
“…Chlorinated phenols, e.g. tetrachloro-and pentachlorophenol, are widely used as biocides [13] and are formed in the pulp mill bleaching process [14][15][16] and during the chlorination of water [17]. Chlorophenols are, moreover, metabolites of other anthropogenic precursors, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…GU is representative of substituted phenols and is of interest as a potential woodsmoke marker in air samples 36. TCA is a representative polyhalogenated aromatic of interest as a disinfection by‐product in drinking water37 and is responsible for cork taint in wines at the parts‐per‐trillion (pptr) levels 38. BP, NA and FL are representative polycyclic aromatic hydrocarbons.…”
mentioning
confidence: 99%